Cortical perfusion as assessed with contrast-enhanced ultrasound is lower in patients with chronic kidney disease than in healthy subjects but increases under low salt conditions. Issue 4 (11th January 2021) - Garessus, Jonas; Brito, Wendy; Loncle, Nicolas; Vanelli, Anna; Hendriks-Balk, Marielle; Wuerzner, Grégoire; Schneider, Antoine; Burnier, Michel; Pruijm, Menno
Abstract: Background: Disturbances in renal microcirculation play an important role in the pathophysiology of chronic kidney disease (CKD), but the lack of easy accessible techniques hampers our understanding of the regulation of the renal microcirculation in humans. We assessed whether contrast-enhanced ultrasound (CEUS) can identify differences in cortical perfusion and alterations induced by different dietary salt intakes in CKD patients and controls. Methods: Participants underwent CEUS twice: once after 5 days of high-salt (HS) intake, and again after 5 days of low salt (LS) diet. Sonovue ® (0.015 mL/kg/min) was perfused as contrast agent and four consecutive destruction–reperfusion sequences were analysed per visit. The primary outcome measure was the (change in) mean perfusion index (PI) of the renal cortex. Results: Forty healthy volunteers (mean age ± standard deviation 50 ± 8 years) and 18 CKD Stages 2–4 patients [aged 55 ± 11 years, estimated glomerular filtration rate (eGFR) 54 ± 28 mL/min/1.73 m 2 ] were included and underwent CEUS without side effects. Under HS conditions, cortical PI was significantly lower in CKD patients [1618 ± 1352 versus 3176 ± 2278 arbitrary units (a.u) in controls, P = 0.034]. Under LS, renal PI increased in CKD patients (with +1098 to 2716 ± 1540 a.u., P = 0.048), whereas PI remained stable in controls. In the continuous analysis, PI correlated with eGFR (Spearman's r  = 0.54, P = 0.005) but not with age, sex, blood pressure or aldosterone levels. Conclusions: CEUS identified important reductions in cortical micro-perfusion in patients with moderate CKD. Lowering salt intake increased perfusion in CKD patients, but not in controls, underlining the benefits of an LS diet in CKD patients. Whether a low PI is an early sign of kidney damage and predicts renal function decline needs further study.